2021
DOI: 10.1021/acscatal.1c01097
|View full text |Cite
|
Sign up to set email alerts
|

Isolating Conformers to Assess Dynamics of Peptidic Catalysts Using Computationally Designed Macrocyclic Peptides

Abstract: Studying the relationship between catalyst conformational dynamics and selectivity in an asymmetric reaction is a challenge. In this study, cyclic peptides were computationally designed to stabilize different ground state conformations of a highly effective, flexible tetrapeptide catalyst for the atroposelective bromination of N-aryl quinazolinones. Through a combination of computational and experimental techniques, we have determined that dynamic movement of the lead catalyst plays a crucial role in achieving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 28 publications
4
40
0
Order By: Relevance
“…These calculated structures provide atomistic pictures that support the plausibility of I R and I S as intermediates. A comprehensive computational assessment of various contingencies for these flexible systems, for example combining molecular dynamics simulations with DFT-level refinement, could well reveal more insight. Nevertheless, the structures of I R and I S ground each as reasonable catalyst–substrate complexes of differing energy along the complex reaction coordinate surface.…”
Section: Resultsmentioning
confidence: 99%
“…These calculated structures provide atomistic pictures that support the plausibility of I R and I S as intermediates. A comprehensive computational assessment of various contingencies for these flexible systems, for example combining molecular dynamics simulations with DFT-level refinement, could well reveal more insight. Nevertheless, the structures of I R and I S ground each as reasonable catalyst–substrate complexes of differing energy along the complex reaction coordinate surface.…”
Section: Resultsmentioning
confidence: 99%
“…However, in asymmetric catalysis, it is well-known that structural rigidity of non-enzymatic chiral catalysts, such as the 2,2′-bis(diphenylphosphino)−1,1′-binaphthyl (BINAP)-metal complexes 3 , 4 and BINOL-based phosphoric acids 5 , 6 shown in Fig. 1c , is usually essential in achieving high levels of asymmetric inductions 7 – 9 and less attention has been paid to the molecular flexibility and conformational dynamics of the chiral catalysts 10 15 . Due to the great difficulty in isolating the conformers, it is very challenging to reveal the relationship between the conformations of chiral catalysts and the enantiodiscrimination.…”
Section: Introductionmentioning
confidence: 99%
“…An Eyring analysis demonstrated that the solvent-dependent enantioselectivity of the conformationally flexible catalyst was a result of switching between an enthalpically and entropically controlled mechanism. Within the realm of organocatalysis, some of the most prolifically studied flexible systems have been small-molecule peptide catalysts. , Recent work by the Miller and Baker groups demonstrated that, in a peptide-catalyzed, atroposelective bromination, , a more flexible peptide enhanced enantioselectivity, as compared to a less flexible analogue (Scheme C) . This outcome resulted from the catalyst’s ability to more easily access selective and reactive catalyst conformations in transition states.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Recent work by the Miller and Baker groups demonstrated that, in a peptide-catalyzed, atroposelective bromination, 10,11 a more flexible peptide enhanced enantioselectivity, as compared to a less flexible analogue (Scheme 1C). 12 This outcome resulted from the catalyst's ability to more easily access selective and reactive catalyst conformations in transition states. Despite these advances, understanding the origins of selectivity in conformationally flexible catalyst systems remains an ongoing challenge.…”
Section: ■ Introductionmentioning
confidence: 99%